The impact of nitric oxide on HER family post-translational modification and downstream signaling in cancer - O’Neill, Ciara E.; Sun, Kai; Sundararaman, Sugunapriyadharshini; Chang, Jenny C.; Glynn, Sharon A. (Frontiers in Physiology, 2024)
The Human Epidermal Growth Factor Receptor (HER) family consists of four members, activated by two families of ligands. They are known for mediating cell-cell interactions in organogenesis and their deregulation have been associated with various cancers including breast and oesophageal. In particular, aberrant EGFR and HER2 signalling drive disease progression and result in poorer patient outcomes. Nitric oxide has been proposed as an alternative activator of the HER family and may play a role in this aberrant activation due to its ability to induce s-nitrosation and phosphorylation of EGFR. This review discusses the potential impact of NO on HER family activation and downstream signalling, alongside its role in the efficacy of therapeutics targeting the family.